PENGELOLAAN KELAS AKSELERASI DI SD Hj. ISRIATI BAITURRAHMAN I SEMARANG - MUSOZIYAH , MUSOZIYAH (2011)
The research’s focus is “How is the characteristics of the management of the acceleration at the Elementary School of Hj. Isriati Baiturrahman I Semarang? The purpose of this study are: (1) to know the characteristics of planning accelerated class, (2) to know the characteristics of the process of implementing accelerated class, (3) to know the characteristics of evaluation system accelerated class. The type of research is qualitative research and with ethnographic design. This research was conducted at the Elementary School of Hj. Isriati Baiturrahman I Semarang. The main subjects are principal of institutional, development institutions and students in the Elementary School of Hj. Isriati Baiturrahman I Semarang. Techniques of data collection used interviews, observation, and documentation. The data analysis starts from (1) data collection, (2) data reduction, (3) display data, and (4) conclution. Validity of data test used the credibility, transferability, conformability and dependability. The results showed that, the characteristics of the management of accelerated class in Hj. Isriati Baiturrahman I Semarang Elementary School includes: (1) the characteristics of the planning of accelerated class in Hj. Isriati Baiturrahman I Semarang Elementary School. The planning program since education office pointed Hj. Israti Elementary School to hold accelerated learning program, report and support for Isriati Foundation. the chronology of the planning process since linkage analysis with the vision mission, then internal and external socialization, and preparation of teachers, students, curriculum and fasilites. (2) the characteristic of the Management process accelerated class in Hj. Isriati Elementary school include: characteristics of the material/subject that are used at acceleration class, the characteristing of teaching and learning strategies which are all adapted to contextual learning methods based on student learning, as well as elimination system to students are not to take part in learning at acceleration class, and adequacy to infrastructure includes the utilization of facilities and infra structure in accordance with the strategy of learning and student-centered learning. (3) the characteristics of the evaluation system includes daily evaluation and semester evaluation. The daily evaluation includes the pre test, post test, home work, and daily test. The semester test includes mid semester test, end of semester test which are all adapted to the classroom-based learning. Final exam along with regular classes, the Elementary School of Hj. Isriati Baiturrahman I Semarang.